Use and Application of Firearms by the Police in the Light of Human Rights Standards in Poland - Fehler, Włodzimierz (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2020)
The article is devoted to the assessment of the rules, possibilities and manners of using and applying firearms by the Police in terms of compliance with human rights. The first part of the study contains analyses focusing on general frames for the use and application of firearms and circumstances giving premises for the use or application of these arms. In the next section, the discussion covers the conduct of law enforcement officials preceding the use of firearms and refers to the question of the so-called special use of firearms. The content of the final part of the article covers mechanisms preventing abuse regarding the use and application of firearms and procedures for situations of breaching legal regulations for the use of such arms. The article closes with the summary where, based on the analyses of existing solutions and available statistical data, a conclusion is made that the Police exercise proper caution so as to ensure the observance of human rights in relation to holding legislative power to use and apply firearms. The key methods applied while preparing this article were the legal analysis and the institutional analysis. In the alternative, a descriptive method with the application of the critical analysis of the literature on the subject was also employed.

Artykuł poświęcony jest ocenie zasad, możliwości oraz sposobów użycia i wykorzystania broni palnej przez Policję w kontekście przestrzegania praw człowieka. W pierwszej części opracowania zawarte zostały analizy poświęcone ogólnym ramom używania i wykorzystania broni palnej oraz okolicznościom stwarzającym przesłanki do użycia lub wykorzystania tej broni. W kolejnym fragmencie rozważania koncentrują się wokół postępowania policjantów poprzedzającego użycie broni palnej oraz odnoszą się do kwestii tzw. specjalnego użycia broni palnej. W końcowej części artykułu znajdują się treści poświęcone: mechanizmom zapobiegającym nadużyciom w zakresie używania i wykorzystywania broni palnej oraz procedurom postępowania w sytuacjach naruszenia prawa dotyczącego użycia i wykorzystania tej broni. Tekst kończy się podsumowaniem, w ramach którego na podstawie analizy istniejących rozwiązań i dostępnych danych statystycznych sformułowano ogólny wniosek o właściwej dbałości Policji o przestrzeganie praw człowieka w związku z posiadaniem ustawowych upoważnień do używania i wykorzystywania broni palnej. Zasadniczymi metodami użytymi przy pisaniu artykułu były analiza prawna oraz analiza instytucjonalna. Pomocniczo zastosowano również metodę opisu połączoną z wykorzystaniem krytycznej analizy literatury przedmiotu.
Wykorzystywanie u używanie broni palnej przez policję w Polsce w świetle norm praw człowieka
Keywords: internal security; individual security; human rights; firearms; the Police; bezpieczeństwo wewnętrzne; bezpieczeństwo jednostki; prawa człowieka; broń palna; Policja